The Influence of Organizational Clarity on the Labor Absorption of Employees in Private Companies in Montería, Colombia - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between organizational clarity and labor absorption in employees of private companies in Montería, Colombia. Organizational clarity refers to employees' perception of the structure, communication, and definition of roles within the company, while labor absorption is the state of total immersion in work tasks, characterized by high levels of concentration and fluidity at work. Using a simple linear regression model, the impact of organizational clarity on labor absorption was evaluated with a sample of 250 employees from different private companies in the city. The results indicated that greater organizational clarity is significantly associated with an increase in work absorption, suggesting that when employees perceive structured organizational processes and effective communication, they experience greater connection to their tasks and greater engagement in their performance. These findings reinforce the importance of organizational management in work motivation and performance, providing empirical evidence on the relevance of well-defined organizational environments to enhance employee engagement.